Orality and literacy : reflections across disciplines - Carlson, Keith, 1966-; Fagan, Kristina Rose, 1973-; Khanenko-Friesen, Natalia (University of Toronto Press, 2011)
"Through topics as diverse as Aboriginal Canadian societies, Ukrainian-Canadian narratives, and communities in ancient Greece, medieval Europe, and twentieth-century Asia, these cross-disciplinary essays reveal the powerful ways in which cultural assumptions, such as those about truth, disclosure, performance, privacy, and ethics, can affect a society's uses of and approaches to both the written and the oral. The fresh perspectives in Orality and Literacy reinvigorate the subject, illuminating complex interrelationships rather than relying on universal generalizations about how literacy and orality function."--Jacket.